Effects of Varieties and Pot Colours on Boosting Capsicum Growth and Yield (Journal of the Bangladesh Agricultural University, 2024)
Heat stress can significantly hinder root growth in containerized plant production, a concern that growers often overlook. One potential solution is using different container colors to minimize the effects of sunlight on the heat balance of growing media. The current varieties of capsicum (Capsicum annuum L.) often exhibit inadequate stress tolerance, limiting capacity for boosting yield in containerized systems. This research investigated the influence of pot colour and variety selection on the growth and productivity of capsicum in a containerized system within subtropical environments. Twelve treatments were tested, including three capsicum varieties ('Intruder', 'Bomby', 'Purple Beauty') and four pot colours (red, black, white, green). Results showed that 'Purple Beauty' capsicum grown in white pots demonstrated superior vegetative growth and phenological attributes compared to those grown in black pots. Soil temperatures at a depth of 5 cm were found to be 3-4°C lower in white pots and highest in black pots. Specifically, 'Purple Beauty' grown in white pots exhibited a 27.3% increase in plant height and a 22.6% larger leaf area compared to 'Intruder' grown in black pots. Twelve weeks post-transplant, the chlorophyll index (SPAD) was 12.1% higher, and shoot and root dry weights were increased by 49.6% and 55.2%, respectively, for 'Purple Beauty' in white pots compared to 'Intruder' in black pots. Additionally, 'Purple Beauty' in white pots showed a 16.1% higher leaf relative water content (LRWC) and 29.7% less electrolyte leakage. Flowering in 'Purple Beauty' grown in white pots began six days earlier, with 25.6% higher fruit sets and 34.8% fewer flower drops compared to 'Intruder' in black pots. Marketable fruit yields for 'Purple Beauty' in white pots were 35.4% higher than those for 'Intruder' in black pots. These findings suggest that 'Purple Beauty' significantly benefits from cultivation in white pots, leading to improved plant growth, reduced heat stress, and enhanced fruit yield in a containerized production system.J Bangladesh Agril Univ 22(4): 412–421, 2024